Walking Pace and the Risk of Cognitive Decline and Dementia in Elderly Populations: A Meta-analysis of Prospective Cohort Studies - Quan, Minghui; Xun, Pengcheng; Chen, Cheng; Wen, Ju; Wang, Yiyu; Wang, Ru; Chen, Peijie; He, Ka (The journals of gerontology. Series A, Biological sciences and medical sciences, 2017)
Data on the longitudinal association of walking pace with the risk of cognitive decline and dementia are inconsistent and inconclusive. Therefore, researchers conducted a meta-analysis of prospective cohort studies to quantitatively assess the association of walking pace with the risk of cognitive decline and dementia among elderly populations. Eligible studies were searched in PubMed and EMBASE through April 22, 2016. Additional information was retrieved through Google Scholar or hand review of the reference lists from the relevant studies. Prospective cohort studies were included if they reported relative risk (RR) and the corresponding 95% confidence interval (CI) of cognitive decline or dementia in relation to walking pace. Seventeen studies were identified, including 10 studies reporting the RR of cognitive decline (9,949 participants and 2,547 events) and 10 presenting the RR of dementia (14,140 participants and 1,903 events). Comparing the lowest to the highest category of walking pace, the pooled RR was 1.89 (95% CI = 1.54-2.31) for cognitive decline and 1.66 (95% CI = 1.43-1.92) for dementia. With every 1 dm/s (360 m/h) decrement in walking pace, the risk of dementia was increased by 13% (RR = 1.13; 95% CI = 1.08-1.18). This meta-analysis provides accumulated evidence supporting that slow or decreased walking pace is significantly associated with elevated risk of cognitive decline and dementia in elderly populations.